Isolation and molecular identification of fungi associated with root rot and head blight of wheat (Triticum aestivum L.) in Ain Al-Tamur district, Karbala province, Iraq - Basheer J. Al_Taie; Rajaa G. Abdalmoohsin; Mushtak T. Mohammadali (Journal of Kerbala for Agricultural Sciences, 2025)
This study was conducted in the Graduate Studies Laboratory of the College of Agriculture, University of Kerbala, with the aim of isolating and identifying fungi associated with root rot and head blight in wheat plants using Polymerase Chain Reaction (PCR) technology. PCR analysis results showed that the most pathogenic isolates were Alternaria infectoria (B9), Fusarium equiseti (K1), Fusarium oxysporum (A4), Fusarium culmorum (SH2), Fusarium equiseti (K6), and Fusarium pseudograminearum (F2). The fungal isolates were registered at the National Center for Biotechnology Information (NCBI) under the accesstion numbers: PV769992.1, PV769993.1, PV769994.1, PV769995.1, PV769996.1, PV770002.1, respectively. The results also showed the frequent occurrence of several species of Fusarium in the studied samples.